The price of healthy and unhealthy foods in Australian primary school canteens - Rebecca Wyse; John Wiggers; Tessa Delaney; Jia Ying Ooi; Josephine Marshall; Tara Clinton‐McHarg; Luke Wolfenden (Elsevier, 2017)
Abstract Objective: To describe the price of Australian school canteen foods according to their nutritional value. Methods: Primary school canteen menus were collected as part of a policy compliance randomised trial. For each menu item, dietitians classified its nutritional value; 'green' ('good sources of nutrients'), 'amber' ('some nutritional value'), 'red' ('lack adequate nutritional value') and assigned a food category (e.g. 'Drinks', 'Snacks'). Pricing information was extracted. Within each food category, ANOVAs assessed differences between the mean price of 'green', 'amber' and 'red' items, and post‐hoc tests were conducted. Results: Seventy of the 124 invited schools participated. There were significant differences in the mean price of 'green', 'amber' and 'red foods' across categories, with 'green' items more expensive than 'amber' items in main‐meal categories ('Sandwiches' +$0.43, 'Hot Foods' +$0.71), and the reverse true for non‐meal categories ('Drinks' −$0.13, 'Snacks' −$0.18, 'Frozen Snacks' −$0.25^). Conclusion: Current pricing may not encourage the purchasing of healthy main‐meal items by and for students. Further investigation of pricing strategies that enhance the public health benefit of existing school canteen policies and practices are warranted. Implications for Public Health: Providing support to canteen managers regarding healthy canteen policies may have a positive impact on public health nutrition.